The effects of dietary folate and iron supplementation on restless legs and preeclampsia in pregnancy - Aynaci, Gülden; Guksu, Zuhal (Progress in Nutrition, 2019)
Introduction: RLS in pregnant women at the beginning of the condition increases the risk of reduced sleep quality, systemic arterial pressure increase, iron and folate deficiency anemia. The most common causes are thought to be physical changes, decreased sleep quality, or organic factors (decreasing folate and iron level). Aim: The aim of this study was to evaluate the role of RLS and its interaction with preeclampsia, anemia, folate deficiency, and low sleep quality. Methods: Our study was conducted between July 2018 and February 2019 in Trakya University Medical Faculty Hospital, Obstetrics Department. Pregnant women with symptoms related to RLS were investigated in terms of sleep quality and preeclampsia. An interview form was completed with the pregnant women during face-to-face interviews. Sociodemographic characteristics were questioned in this form. The IRLSGG criteria were used for RLS evaluations. The sleep quality of the participants was assessed using the PSQI. The iron status of pregnant women was questioned. Pregnant women were asked whether they received prophylactic iron medication. Results: Three hundred twenty-four volunteer pregnant women who presented to the obstetrics clinic of Trakya University Medical Faculty Hospital were included in the study. The mean age of the pregnant women in the study was 29.18±6.19 years. There was no statistically significant difference when we compared pregnant women with and without RLS when asked about their BMI in pre-gestational periods. The average use of iron medication of the women with RLS was 3 days or less per week. There was a significant difference between women with and without RLS regarding iron prophylaxis. The evaluation of the relationship between RLS, sleep quality, and preeclampsia in the pregnant women showed that RLS and PSQI levels had statistically significant differences according to trimesters. Discussion: Our study evaluated the frequency of RLS, the relationship between RLS and preeclampsia, and the relationship between RLS and sleep quality in pregnant women. RLS is more common in pregnant women who do not receive iron support. Low iron levels contribute to the development of RLS. Clinical and laboratory (hemoglobin) analysis revealed some differences between the groups. As the hemoglobin levels and iron supplementation decreased, the incidence of RLS symptoms was found to increase. For the treatment of RLS, non-pharmacologic treatments in pregnant women should be considered first; however, the use of iron medication is usually recommended. After the iron requirement is met, additional treatment planning should be made by investigating whether the RLS symptoms have regressed. Therefore, it was concluded that RLS was related to BMI and hemoglobin level differences. During pregnancy, the recommended dietary allowance (RDA) for folate is 600 µg/day of dietary folate equivalent. Natural folate with foods and folate supplementation since pregnancy may help to prevent fetal morbidity. The major sources of dietary folate are citrus fruits and juices, legumes, whole-wheat bread, and green leafy vegetables. To prevent fetal morbidities, women planning childbirth or pregnant should consume 400 µg per day of synthetic folic acid from natural foods (cereals and other grains), or supplement drugs. Pregnant women may need advice from a physician or a qualified dietetics professional to follow nutritional guidelines, especially for folate and iron. Pregnant women; must be provided a wide range of nutrition quality and evaluation. We suggest that more studies are needed to assess the relationship between low quality of sleep, iron and folate supports in nutrition, RLS symptoms, and/or preeclampsia. Conclusion: Our study demonstrates the need to establish quality care and interventions for the protection of both maternal and fetal health due to poor sleep quality and RLS symptoms during pregnancy. Pregnant women should be presented with a variety of evidence-based patient care interventions. In the presence of RLS, signs of systemic arterial hypertension and iron supplementation in pregnant women should be examined carefully and if necessary, pregnancy interventions should be added.